Cofaced Organizational and Technological Innovation Theory: Interaction of Innovation Practitioners for Continuity of Defensive Innovative Business - Iraj Masoomi Baran; Manochehr Manteghi; Alireza Booshehri; Gholam Reza Tavakoli (بهبود مدیریت, 2020)
Constantly responding to the diverse needs of the Armed Forces' air and space sectors requires the continuation and development of innovative defense business. This has led executives to strive for organizational innovation to optimize or produce new military products.The purpose of the research is“presentation of cofaced organizational and technological innovation theory based on the interaction of innovation practitioners”to answer, weak sustain and interaction of innovation trustees for systematic continuation of  innovative business in large defensive industrial organizations with air and missile products so that between 1394 and 1398, using "Systematic Grounded Theory" method for related purpose. The data from this study was conducted through Semi structured interviews with 19 live-experienced experts in the organizations. To collect data, interviews were conducted on the basis of a purposive sampling method with senior vice president, research and innovation deputies and the deputies of plan, program and budget. Then, using the snowball sampling method and other participants were selected and more data were collected. The results of the data analysis during: open, axial and selective coding, resulted in the form of 12 categories based on the paradigm model including: extent of changes, diversity of needs, expectations of defensive stakeholders, organizational learning, national and international capacities, complexity of environmental factors, capabilities and limitations of defensive organizations, continuity and excellency of innovative business, promoting nontechnological innovations and development technological defense innovation, improving the defense economy and increase deterrence power and by writing the relevant story line\historical narretive, finally cofaced innovation theory and 12 related hypotheses were constructed. Also their application can provide a better understanding and improvement of the common literature of defense stakeholders.